2018
DOI: 10.1007/s11064-018-2620-x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Pathology and Gut Microbiota Alterations in a Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Mouse Model of Parkinson’s Disease

Abstract: Patients with Parkinson's disease (PD) often have non-motor symptoms related to gastrointestinal (GI) dysfunction, such as constipation and delayed gastric emptying, which manifest prior to the motor symptoms of PD. Increasing evidence indicates that changes in the composition of the gut microbiota may be related to the pathogenesis of PD. However, it is unclear how GI dysfunction occurs and how gut microbial dysbiosis is caused. We investigated whether a neurotoxin model of PD induced by chronic low doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 48 publications
6
79
1
Order By: Relevance
“…However, according recent studies, MPTP can also produce DAergic selective neuron toxins in the enteric nervous system of animal models, causing damage and pathology in the gastrointestinal nerves [44][45][46]. Interestingly, Feng Lai and his colleagues found that MPTP caused gastrointestinal dysfunction and intestinal pathology prior to motor dysfunction, which explains the Braak staging theory that pathogenesis of PD from the gut to the brain [47]. The studies in consistent with this theory demonstrated that α-synuclein appears in the enteric nervous system during the early stages of PD, and this misfolded protein may spread to the central nervous system through the vagus nerve, resulting in nerve damage in the SN [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, according recent studies, MPTP can also produce DAergic selective neuron toxins in the enteric nervous system of animal models, causing damage and pathology in the gastrointestinal nerves [44][45][46]. Interestingly, Feng Lai and his colleagues found that MPTP caused gastrointestinal dysfunction and intestinal pathology prior to motor dysfunction, which explains the Braak staging theory that pathogenesis of PD from the gut to the brain [47]. The studies in consistent with this theory demonstrated that α-synuclein appears in the enteric nervous system during the early stages of PD, and this misfolded protein may spread to the central nervous system through the vagus nerve, resulting in nerve damage in the SN [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with drugs that cause Parkinson's disease-like damage to the dopamine neuronal system, reported that they also induce gut dysbiosis [65,66]. This microbial imbalance was evidenced by increases in Enterobacteriaceae, and particularly of Proteus mirabilis, a species within this family [67].…”
Section: Discussionmentioning
confidence: 99%
“…motor deficits (Lai et al, 2018). These studies are still mostly associative, although the presence of dysbiosis in multiple animal models strengthens the claim of GI dysfunction as a core aspect of disease.…”
Section: ) Depression and Anxietymentioning
confidence: 88%
“…Intriguingly, some of the changes in microbial composition in these rotenone‐exposed mice were similar to alterations observed in human PD patients. Alterations in gut microbiota composition as well as GI dysfunction were found in another toxicological model of PD, MPTP (Methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine) exposure, with GI abnormalities including intestinal α‐synuclein pathology preceding motor deficits (Lai et al ., ). These studies are still mostly associative, although the presence of dysbiosis in multiple animal models strengthens the claim of GI dysfunction as a core aspect of disease.…”
Section: Neurological Disordersmentioning
confidence: 97%